High-entropy perovskite oxide catalyst and preparation method and application thereof

By doping high electronegative transition metal elements into perovskite oxide catalysts and preparing nanorod-like structures, the problems of slow OER kinetics and scarcity of precious metal catalysts are solved, and efficient OER catalytic performance is achieved.

CN119456053APending Publication Date: 2025-02-18TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411943645.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The kinetics of oxygen evolution reaction (OER) in existing electrochemical water decomposition is slow, and the scarcity and durability of precious metal-based electrocatalysts are not ideal, which limits their wide application.

Method used

Using the high entropy perovskite oxide catalyst La(MMn)O3, doping the B site through high electronegative transition metal elements to enhance the covalence of Mn-O, and nanometers are prepared by electrospinning and calcining. The rod-like structure of particles accumulates, increasing the surface area of ​​the catalyst.

Benefits of technology

The catalytic performance is significantly improved. La(NiCuCoFeMn)O3 catalyst exhibits excellent activity in OER, with an overpotential of 328mV, lower charge transfer energy, stronger Mn-O covalent, and stable catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456053A_ABST
    Figure CN119456053A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy perovskite oxide catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalysts. The chemical general formula of the high-entropy perovskite oxide catalyst is La (MMN) O3, and M is a transition metal element with high electronegativity. M is a mixture of Ni, Cu, Co and Fe elements. The molar ratio of La to Ni to Cu to Co to Fe to Mn is (0.9 to 1): (0.15 to 0.25): (0.15 to 0.25): (0.15 to 0.25): (0.15 to 0.25): (0.15 to 0.25): (0.15 to 0.25). The La (MMN) O3 catalyst is of a rod-shaped structure formed by stacking particles. According to the high-entropy perovskite oxide catalyst as well as the preparation method and the application thereof, the B site of perovskite is doped by the high-electronegativity transition metal element, so that the Mn-O covalence is enhanced, and the catalytic performance is improved; the catalyst is prepared in an electrostatic spinning and calcining mode, a rod-shaped structure with accumulated nano-particles is obtained, the surface area of the catalyst is increased, and the catalytic effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and in particular to a high entropy perovskite oxide catalyst and a preparation method and application thereof. Background Art

[0002] Electrochemical water splitting using renewable electricity is a green route to produce high-purity hydrogen. The oxygen evolution reaction (OER) is the core half-reaction of electrochemical water splitting. However, the kinetics of OER are relatively slow due to its complex four-electron transfer mechanism. Although noble metal-based electrocatalysts have shown excellent activity in OER, their widespread application is hindered by their scarcity and unsatisfactory durability. Therefore, it is imperative to explore abundant transition metal-based electrocatalysts.

[0003] Perovskite oxides (ABO3), composed of alkaline or rare earth elements at the A-site and transition metal elements at the B-site, have attracted extensive attention due to their low cost, flexible composition, and adjustable physicochemical and catalytic properties, making perovskite-based catalysts promising for OER applications. For ABO3 perovskite oxides, the B-site cation is generally considered to be the reaction center. The BO covalency reflects the binding strength of the surface adsorbed species and is an important descriptor of alkaline OER activity. Optimizing the BO interaction is necessary to improve catalytic activity and reaction kinetics. Therefore, adjusting the metal-oxygen covalency is an effective way to optimize catalyst performance. Summary of the invention

[0004] The purpose of the present invention is to provide a high entropy perovskite oxide catalyst and a preparation method and application thereof, wherein the B position of the perovskite is doped with a high electronegative transition metal element to enhance the Mn-O covalency and improve the catalytic performance; the catalyst is prepared by electrospinning and calcination to obtain a rod-like structure of nanoparticle accumulation, thereby increasing the surface area of ​​the catalyst and improving the catalytic effect.

[0005] To achieve the above objectives, the present invention provides a high entropy perovskite oxide catalyst, the general chemical formula of which is La(MMn)O3, where M is a transition metal element with high electronegativity.

[0006] Preferably, M is a mixture of Ni, Cu, Co and Fe elements.

[0007] Preferably, the molar ratio of La, Ni, Cu, Co, Fe and Mn is 0.9-1:0.15-0.25:0.15-0.25:0.15-0.25:0.15-0.25:0.15-0.25:0.15-0.25, more preferably 1:0.2:0.2:0.2:0.2:0.2.

[0008] Preferably, the La(MMn)O3 catalyst is a rod-like structure of accumulated particles.

[0009] The method for preparing the high entropy perovskite oxide catalyst comprises the following steps: S1, dissolving lanthanum, nickel, copper, cobalt, iron, and manganese metal salts in a mixed solvent of dimethylformamide and deionized water to prepare a metal ion mixed solution; S2, adding polyvinyl pyrrolidone and polyvinyl alcohol to the metal ion mixed solution, and stirring to obtain an electrospinning solution; S3, adding the electrospinning solution into an electrospinning device for electrospinning to obtain a precursor; S4, calcining the precursor and cooling it to room temperature to obtain a catalyst.

[0010] Preferably, in S1, the metal salt is nitrate or sulfate, the total concentration of metal ions in the metal ion mixed solution is 0.2 mol / L~0.3 mol / L, more preferably 0.2 mol / L; the volume ratio of dimethylformamide to deionized water is (2~5):1, more preferably (3~4):1.

[0011] Preferably, in S2, the molecular weight of polyvinyl pyrrolidone is 30,000-45,000; the molecular weight of polyvinyl alcohol is 60,000-80,000; the mass ratio of polyvinyl pyrrolidone to polyvinyl alcohol is (1.5-2.5):1; the stirring temperature is 20°C-60°C, more preferably 30°C-60°C; the stirring time is 12h-24h, more preferably 12h-18h.

[0012] Preferably, in S3, the electrospinning equipment parameters are: voltage 12kV~18kV, rate 0.0002mm / s~0.001mm / s, distance between needle and roller 5cm~12cm, inner diameter of needle 0.2mm~0.6mm. More preferably: voltage 12kV~15kV, rate 0.0005 mm / s, distance between needle and roller 5cm~7cm, inner diameter of needle 0.3mm~0.4mm. The present invention realizes the regulation of precursor fiber diameter by controlling the voltage, rate, distance, and inner diameter of needle.

[0013] The diameter of the precursor fiber is 100nm~200nm, preferably 100nm~150nm.

[0014] Preferably, in S4, the calcination temperature is 550°C to 800°C, more preferably 600°C to 700°C; and the calcination time is 2h to 4h, more preferably 3h.

[0015] The heating rate of the calcination temperature from room temperature to the calcination temperature is 2°C / min to 10°C / min, more preferably 5°C / min; the calcination atmosphere is preferably air; and the calcination is preferably carried out in a tubular furnace.

[0016] The above catalyst is used as an oxygen evolution catalyst.

[0017] The advantages and positive effects of the high entropy perovskite oxide catalyst and its preparation method and application described in the present invention are: 1. The present invention uses highly electronegative transition metal elements to dope the B site, which effectively improves the binding strength of the surface adsorbed substances and improves the catalytic performance. The La(NiCuCoFeMn)O3 catalyst has excellent OER performance with an overpotential of 328mV. The La(NiCuCoFeMn)O3 catalyst has lower charge transfer energy, stronger Mn-O covalency, and good OER catalytic performance.

[0018] 2. The catalyst described in the present invention has a rod-like structure morphology of accumulated particles, which increases the specific surface area of ​​the catalyst and can also provide more active sites, which is beneficial to improving the catalytic performance.

[0019] 3. The preparation method of the high entropy perovskite oxide catalyst provided by the present invention is simple and easy to operate, can be synthesized in batches, and the synthesized high entropy perovskite oxide catalyst exhibits good oxygen evolution activity and stable catalytic performance.

[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The La(NiCuCoFeMn)O3 prepared in Example 1 and the LaMnO3 prepared in Comparative Example 1 are and the XRD curve of La(NiCuCoMnSc)O3 prepared in Comparative Example 2; Figure 2 This is a SEM image of La(NiCuCoFeMn)O3 prepared in Example 1; Figure 3 The La(NiCuCoFeMn)O3 prepared in Example 1, the LaMnO3 prepared in Comparative Example 1 and Linear sweep voltammetry curve of electrocatalytic oxygen evolution of La(NiCuCoMnSc)O3 prepared in Comparative Example 2; Figure 4 The La(NiCuCoFeMn)O3 prepared in Example 1, the LaMnO3 prepared in Comparative Example 1 and Electrochemical impedance curve of La(NiCuCoMnSc)O3 prepared in Comparative Example 2; Figure 5 The electrocatalytic oxygen evolution stability curve of La(NiCuCoFeMn)O3 prepared in Example 1; Figure 6 The water electrolysis performance curve of La(NiCuCoFeMn)O3 prepared in Example 1; Figure 7 The Mn element state density curves of La(NiCuCoFeMn)O3 prepared in Example 1 and LaMnO3 prepared in Comparative Example 1; Figure 8 The O element state density curves of La(NiCuCoFeMn)O3 prepared in Example 1 and LaMnO3 prepared in Comparative Example 1. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0023] A high entropy perovskite oxide catalyst has a general chemical formula of La(MMn)O3, where M is a transition metal element with high electronegativity.

[0024] M is a mixture of Ni, Cu, Co and Fe elements.

[0025] The molar ratio of La, Ni, Cu, Co, Fe and Mn is 0.9~1:0.15~0.25:0.15~0.25:0.15~0.25:0.15~0.25:0.15~0.25.

[0026] The choice of metal elements affects the catalytic performance of the catalyst. The covalency between metals with different electronegativity and oxygen is different. Higher metal-oxygen covalency can enhance the binding strength of surface adsorbed substances and reduce the charge transfer energy. The present invention uses a high electronegative transition metal element to dope the B position, which effectively increases the binding strength of surface adsorbed substances and improves the catalytic performance.

[0027] The La(MMn)O3 catalyst is a rod-shaped structure of particle stacking. The rod-shaped structure of particle stacking can increase the specific surface area of ​​the catalyst and provide more active sites, which is beneficial to improving the catalytic performance.

[0028] A method for preparing a high entropy perovskite oxide catalyst comprises the following steps: S1. Dissolve lanthanum, nickel, copper, cobalt, iron and manganese metal salts in a mixed solvent of dimethylformamide and deionized water to prepare a metal ion mixed solution.

[0029] The metal salt is nitrate or sulfate, and the total concentration of metal ions in the metal ion mixed solution is 0.2 mol / L~0.3 mol / L; the volume ratio of dimethylformamide to deionized water is (2~5):1.

[0030] S2. Add polyvinyl pyrrolidone and polyvinyl alcohol into the metal ion mixed solution, and stir to obtain an electrospinning solution.

[0031] The molecular weight of polyvinyl pyrrolidone is 30000~45000; the molecular weight of polyvinyl alcohol is 60000~80000; the mass ratio of polyvinyl pyrrolidone to polyvinyl alcohol is (1.5~2.5):1; the stirring temperature is 20℃~60℃, and the stirring time is 12h~24h.

[0032] S3, adding the electrospinning solution into an electrospinning device for electrospinning to obtain a precursor.

[0033] The parameters of the electrospinning equipment are: voltage 12kV~18kV, speed 0.0002mm / s~0.001mm / s, distance between needle and roller 5cm~12cm, inner diameter of needle 0.2mm~0.6mm.

[0034] S4, calcining the precursor and cooling it to room temperature to obtain a catalyst.

[0035] The calcination temperature is 550℃~800℃, and the time is 2h~4h.

[0036] Example 1 0.325 g of lanthanum nitrate, 0.06 g of iron nitrate, 0.044 g of cobalt nitrate, 0.044 g of nickel nitrate, 0.029 g of copper nitrate and 0.038 g of manganese nitrate were weighed and dissolved in a mixed solvent of 6 ml of deionized water and 1.5 ml of dimethylformamide to obtain a metal ion mixed solution.

[0037] 0.8 g of polyvinyl pyrrolidone and 0.4 g of polyvinyl alcohol were weighed and added into the metal ion mixed solution, and the electrospinning solution was obtained after stirring at 30° C. for 12 h.

[0038] The electrospinning solution was added to the electrospinning equipment for electrospinning to obtain a precursor. The electrospinning parameters were as follows: voltage 15 kV, rate 0.0005 mm / s, distance between the needle and the roller 7 cm, and inner diameter of the needle 0.34 mm.

[0039] The precursor was placed in an alumina crucible, heated to 600°C in a tube furnace at a heating rate of 5°C / min, and calcined for 2 hours. After cooling to room temperature, a high-entropy perovskite-type La(NiCuCoFeMn)O3 powder was obtained, which was recorded as La(NiCuCoFeMn)O3.

[0040] Comparative Example 1 The difference between this comparative example and Example 1 is that only 0.325 g of lanthanum nitrate and 0.189 g of manganese nitrate are weighed to obtain LaMnO3 powder, which is recorded as LaMnO3.

[0041] Comparative Example 2 The difference between this comparative example and Example 1 is that 0.325 g of lanthanum nitrate, 0.044 g of cobalt nitrate, 0.044 g of nickel nitrate, 0.029 g of copper nitrate, 0.038 g of manganese nitrate and 0.038 g of scandium nitrate are weighed to obtain La(NiCuCoMnSc)O3 powder, recorded as La(NiCuCoMnSc)O3.

[0042] Figure 1 XRD curves of La(NiCuCoFeMn)O3 prepared in Example 1, LaMnO3 prepared in Comparative Example 1, and La(NiCuCoMnSc)O3 prepared in Comparative Example 2. Figure 1 It can be seen that La(NiCuCoFeMn)O3, LaMnO3 and La(NiCuCoMnSc)O3 are all pure phase cubic perovskite structures.

[0043] Figure 2 This is a SEM image of La(NiCuCoFeMn)O3 prepared in Example 1. Figure 2 As can be seen in the figure, La(NiCuCoFeMn)O3 has a nanorod-like microstructure formed by interconnected nanoparticles.

[0044] Figure 3 The linear sweep voltammetric curves of electrocatalytic oxygen evolution of La(NiCuCoFeMn)O3 prepared in Example 1, LaMnO3 prepared in Comparative Example 1 and La(NiCuCoMnSc)O3 prepared in Comparative Example 2 are shown in FIG. Figure 3 It can be seen that the overpotentials of La(NiCuCoFeMn)O3, LaMnO3 and La(NiCuCoMnSc)O3 are 328mV, 407mV and 380mV respectively. The overpotentials of La(NiCuCoFeMn)O3 and La(NiCuCoMnSc)O3 are both lower than that of LaMnO3, indicating that the doping of highly electronegative elements causes electronic interaction between the elements, which is beneficial to improving the catalytic activity.

[0045] Figure 4 Electrochemical impedance curves of La(NiCuCoFeMn)O3 prepared in Example 1, LaMnO3 prepared in Comparative Example 1, and La(NiCuCoMnSc)O3 prepared in Comparative Example 2. Figure 4It can be seen that the charge transfer impedances of La(NiCuCoFeMn)O3, LaMnO3 and La(NiCuCoMnSc)O3 are 16.1 Ω, 67.8 Ω and 54.7 Ω respectively, among which La(NiCuCoFeMn)O3 has the smallest charge transfer impedance, indicating that La(NiCuCoFeMn)O3 prepared in Example 1 has higher electrical conductivity and faster charge transfer rate.

[0046] Figure 5 This is the electrocatalytic oxygen evolution stability curve of La(NiCuCoFeMn)O3 prepared in Example 1. Figure 5 It can be seen that during the test period of up to 30 hours, the voltage remained almost unchanged, indicating that the La(NiCuCoFeMn)O3 prepared in Example 1 has excellent catalytic stability.

[0047] Figure 6 The electrolysis performance curve of La(NiCuCoFeMn)O3 prepared in Example 1. Figure 6 As can be seen from the figure, the LaM3MnFeO3Pt / C hydrolysis device composed of La(NiCuCoFeMn)O3 as anode and commercial Pt / C as cathode has a current density of 10mA / cm 2 The required voltage is 1.61 V, indicating that the La(NiCuCoFeMn)O3 catalyst prepared in Example 1 can be used in a water electrolysis device and has excellent performance.

[0048] Figure 7 The Mn element state density curves of La(NiCuCoFeMn)O3 prepared in Example 1 and LaMnO3 prepared in Comparative Example 1 are as follows: Figure 8 The O element state density curves of La(NiCuCoFeMn)O3 prepared in Example 1 and LaMnO3 prepared in Comparative Example 1. Figure 7 , Figure 8 It can be seen that compared with LaMnO3, the d-band center of Mn in La(NiCuCoFeMn)O3 is closer to the Fermi level, indicating that it has a stronger adsorption capacity for intermediates. In addition, the charge transfer energy between Mn and O in La(NiCuCoFeMn)O3 is 0.91eV, which is significantly smaller than 1.5eV of LaMnO3, indicating that the doping of highly electronegative elements leads to enhanced Mn-O covalency, which is beneficial to the charge transfer between active sites and reaction intermediates.

[0049] Therefore, by using the high entropy perovskite oxide catalyst and its preparation method and application described in the present invention, the B position of the perovskite is doped with a high electronegative transition metal element to enhance the Mn-O covalency and improve the catalytic performance; the catalyst is prepared by electrospinning and calcination to obtain a rod-like structure of nanoparticle stacking, thereby increasing the surface area of ​​the catalyst and improving the catalytic effect.

[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A high entropy perovskite oxide catalyst, characterized in that: Its general chemical formula is La(MMn)O3, where M is a transition metal element with high electronegativity; The M is a mixture of Ni, Cu, Co and Fe elements; The molar ratio of La, Ni, Cu, Co, Fe and Mn is 0.9-1: 0.15-0.25: 0.15-0.25: 0.15-0.25: 0.15-0.25: 0.15-0.25; The La(MMn)O3 catalyst is a rod-like structure of accumulated particles.

2. The method for preparing a high entropy perovskite oxide catalyst according to claim 1, characterized in that: The following steps are involved: S1, dissolving lanthanum, nickel, copper, cobalt, iron, and manganese metal salts in a mixed solvent of dimethylformamide and deionized water to prepare a metal ion mixed solution; S2, adding polyvinyl pyrrolidone and polyvinyl alcohol to the metal ion mixed solution, and stirring to obtain an electrospinning solution; S3, adding the electrospinning solution into an electrospinning device for electrospinning to obtain a precursor; S4, calcining the precursor and cooling it to room temperature to obtain a catalyst; In S1, the metal salt is nitrate or sulfate, the total concentration of metal ions in the metal ion mixed solution is 0.2 mol / L~0.3 mol / L; the volume ratio of dimethylformamide to deionized water is (2~5):

1.

3. The method for preparing a high entropy perovskite oxide catalyst according to claim 2, characterized in that: In S2, the molecular weight of polyvinyl pyrrolidone is 30000-45000; the molecular weight of polyvinyl alcohol is 60000-80000; the mass ratio of polyvinyl pyrrolidone to polyvinyl alcohol is (1.5-2.5):1; the stirring temperature is 20°C-60°C, and the stirring time is 12h-24h.

4. The method for preparing a high entropy perovskite oxide catalyst according to claim 2, characterized in that: In S3, the electrospinning equipment parameters are: voltage 12kV~18kV, speed 0.0002mm / s~0.001mm / s, distance between needle and roller 5cm~12cm, inner diameter of needle 0.2mm~0.6mm; The diameter of the precursor fiber is 100nm~200nm.

5. The method for preparing a high entropy perovskite oxide catalyst according to claim 2, characterized in that: In the S4, the calcination temperature is 550°C to 800°C, the heating rate is 2°C / min to 10°C / min, and the calcination time is 2h to 4h.

6. A high entropy perovskite oxide catalyst according to claim 1, characterized in that: The catalyst is used as an oxygen evolution catalyst.

Citation Information

Patent Citations

  • Treatment method for improving electrochemical performance of B-site doped perovskite catalyst

    CN109888315A

  • Network doped perovskite catalyst and preparation method and application thereof

    CN109967068A

  • Catalyst for electrochemical water decomposition reaction, and preparation method thereof

    CN111330583A

  • High-entropy perovskite hollow nanotube efficient oxygen evolution reaction catalytic material and preparation method thereof

    CN113061934A

  • Method for preparing perovskite type persulfate catalyst by using electrostatic spinning process

    CN115106091A

Cited By

  • B-site doped medium-entropy lanthanum nickelate ceramic spraying powder and preparation method thereof

    CN120025169A

  • A B-site doped medium-entropy lanthanum nickelate ceramic spray powder and preparation method thereof

    CN120025169B

  • High-entropy perovskite composite photocatalytic material for carbon dioxide reduction as well as preparation method and application of high-entropy perovskite composite photocatalytic material

    CN120644192A

  • High-entropy perovskite material and preparation method and application thereof

    CN120649063A